Individuals' perspectives of causes and influences on their diagnosed anxiety disorders : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Birrell, Lyn (Massey University, 2013)
Anxiety disorders are the most common type of mental disorder in New Zealand, as they are in the Western world. However, little research has been done on how persons with anxiety disorder conceptualize their respective diagnoses. This small community based, qualitative study interviewed seven individuals diagnosed with anxiety disorders and tried to capture the content and complexity of their disorder. Volunteer participants responded to a flyer placed at an anxiety disorders clinic, located in Auckland, New Zealand. Participants included one male and six females, aged from mid 20 to early 40s. Criteria for participation included being diagnosed with an anxiety disorder by a health professional. Participants generally spoke in terms of their problems in living, as well as the development and course of their disorder. All participants reported that (1) their disorder was chronic and pervasive; (2) their condition was debilitating at times; (3) their condition was complicated by depression; and (4) dysfunction or disruption was present in their early family life. Most participants talked about the early onset of disorder. Recognizing and acting on the need for help was problematic for most participants. Thematic analysis was undertaken to best account for the data, which unfolded as a coherent, consistent and holistic narrative. Three common broad developmental themes were identified: traumatic early life, troubled school life and problems with living. Two broad themes were created to capture participants’ thoughts and feelings following diagnosis: rationalisation and post-rationalisation. Discussion specifically suggested the need for further research into the aetiology of anxiety disorders, including the role of maternal controlling behaviour and early onset of the disorder. Further research is also needed to understand and facilitate the help-seeking process for persons suffering from anxiety disorders. A need was identified for the accurate detection of anxiety disorders, particularly when masked by a presentation of depression or other symptoms. Findings suggest that a developmental/ social/contextual model may be most useful in conceptualizing and guiding prevention, intervention and treatment plans. In addition, the impact and meaning of the diagnostic event on people with anxiety disorders requires examination to fully understand all the dynamics and ramifications. Implications from this study include the need for initiatives to aid early recognition and generally to educate people about the nature of anxiety disorders, including the fact that they are common, serious and treatable.
Keywords: Anxiety disorders; Etiology; Aetiology; Patients; Case studies